A South Carolina Chronology - Edgar, Walter B., 1943-; Taylor, C. James, 1945-; Morris, J. Brent (Book collections on Project MUSE., 2020)
"The third edition of A South Carolina Chronology, first published in 1973 and again in 1994. It offers a year-by-year chronology with landmark dates and events in South Carolina's history recorded. The current edition is divided into eight parts and not only adds nearly thirty-years of events that have occurred since the publication of the second edition, but also offers important updates to the material that is covered. While the previous edition mentioned pre-contact South Carolina in a short introductory section, the current edition begins with the section, "Peopling the Continent (17,200 BCE-1669)." It makes a greater effort to acknowledge the extent to which the lands where Europeans arrived in the 15th-17th centuries had long been inhabited by not only people, but complex societies and sociopolitical networks. Indeed, throughout the volume, the editors work to incorporate a more inclusive understanding of what and who constitutes the events and people that are central to the history of the state. In addition to the new broader reading of events that expands the previously chronicled period to take more notice of race, gender, and other social issues, a generation of notable changes and remarkable events have also added measurably to South Carolina's history and this chronology"--